Assessment of the potential for using PET waste as geomaterials in soil micro-reinforcement - Carlos J.P. Graça; Luís M. Ferreira-Gomes; Luis Andrade Pais; Antonio Albuquerque; Maria Vitoria Morais; André Studart; Leonardo Marchiori (Geosystems and Geoenvironment)
The use of synthetic fibers to enhance soil properties is a growing area of research. This study investigates the incorporation of granulated polyethylene terephthalate (PET) waste – derived from crushed plastic soda bottles – into dune sand at 3 % and 5 % ratios to develop a novel composite material and promote PET fiber reuse as a sustainable solution. By valorizing PET waste, this approach reduces plastic pollution and mitigates the demand for natural resource extraction. Physical and mechanical characterization tests, including specific gravity, particle size distribution, normal proctor compaction, direct shear (DS), consolidated isotropic drained (CID) triaxial, and oedometric tests, were conducted on the dune sand, soil-PET mixtures, and pure PET residue. Results demonstrate that the addition of PET significantly influences the friction angle of the composite material, as evidenced by DS and triaxial CID tests. Specifically, the soil-PET mixtures exhibited enhanced shear strength compared to pure sand, while introducing 5 % of PET, the internal friction angle increased up to 12 % and 22 %, according to DS and CID triaxial tests, respectively, maintaining cohesionless behavior. These improvements are attributed to the reinforcing effect and interlocking behavior of PET particles within the sand matrix. The results indicate that PET addition enhances the shear strength and stability of sandy soils, supporting its use in earthworks. This study highlights the dual environmental and mechanical advantage of PET micro-reinforcement, providing a feasible route for plastic waste reuse in geotechnical engineering.